Research Landscape of "European Sculpture" - A Bibliometric Analysis Based on Web of Science Database (2000-2024) - Poologanathan, P.; Thelaxsan, T. (University of Jaffna, 2024)
European sculpture refers to the sculptural traditions that have emerged from the various cultures and regions of Europe throughout history. It encompasses a rich and diverse array of artistic expressions spanning different periods, styles, and cultural contexts. This study attempts to analysis the research publications on European Sculpture from 2000 to 2024 sourced from Web of Science database using search term as title ‘’European Sculpture’’. Totally, 271 documents were received from Web of Science database. Received data were analyzed by HistCite, VOSviewer and MS-Excel software, and these analyses included country- wise research output, Journal- wise, Institution-wise, Subject-wise, Citation-wise, Documents-wise, and Authors-wise. Totally n=271 records has been retrieved with 1,976 total global citations, 7.29 average citations per item and overall h- index is 24. Maximum number of publications has been produced in the year 2020 with 21 (8%) publications and most number of publications has been produced by USA 39 (14%) and the most commonly used key word is Sculpture, it is occurred in 46 records in the research. This study may more helpful the librarian and researchers related to sculptural study to find out further information and continue the future study about ‘’European Sculpture’’.
Keywords: Sculpture; European sculpture; Bibliometric; Artistic expressions; Web of Science